Defense interplay of the zinc-oxide nanoparticles and melatonin in alleviating the arsenic stress in soybean (Glycine max L.). (February 2022) - Bhat, Javaid Akhter; Faizan, Mohammad; Bhat, Masroor Ahmad; Huang, Fang; Yu, Deyue; Ahmad, Ajaz; Bajguz, Andrzej; Ahmad, Parvaiz
Abstract: Present study showed the successful application of the modified hydrothermal method for synthesizing the zinc oxide nanoparticles (ZnO-NPs) efficiently. Well as -synthesized ZnO-NPs are analyzed for various techniques viz., X-ray diffraction (XRD), SEM micrographs, EDAX/Mapping pattern, Raman Spectroscopy Pattern, UV, Photoluminescence (PL) and X-ray photoemission spectroscopy (XPS) analysis. All these measurements showed that ZnO-NPs are highly pure with no internal defects, and can be potentially used in the plant applications. Hence, we further determined the effect of these nanoparticles and melatonin for the modulation of the As tolerance in soybean plants by examining the various growth attributes and metabolic parameters. Our results demonstrated that As-stress inhibited growth (∼34%), photosynthesis-related parameters (∼18–28%) and induced ROS accumulation; however, all these attributes are substantially reversed by the ZnO-NPs and melatonin treatments. Moreover, the As stress induced malondialdehyde (MDA; 71%) and hydrogen peroxide (H2 O2 ; 82%) are partially reversed by the ZnO-NPs and melatonin in the As-stressed plants. This might have resulted due to the ZnO-NPs and melatonin induced activities of the antioxidants plant defense. Overall, the ZnO-NPs and melatonin supplementation separately and in combination positively regulated the As tolerance in soybean; however, the effect of their combined application on the As tolerance was more profound relative to the individual application. These results suggested the synergetic effect of the ZnO-NPs and melatonin on the As tolerance in soybean. However, the in-depth mechanism underlying the defense crosstalk between the ZnO-NPs and melatonin needs to be further explored. Graphical abstract: Image 1 Highlights: Arsenic toxicity inhibited growth, photosynthesis in soybean plants. Oxidative stress biomarkers, MDA and H2 O2 were also enhanced under As toxicity. Antioxidants and other biochemical attributes showed fluctuations in their synthesis under As stress. ZnO-NPs and melatonin individually and in combination enahnced As tolerance. Combined effect of ZnO-NPs and melatonin were more effective than their individual effect in alleviating As toxicity.